Evaluation of the immunogenicity of a Crimean-Congo hemorrhagic fever virus vaccine candidate in mice developed based on a baculovirus Zera nanoparticle delivery system - Zhang, Gang; Wang, Pu; Jiang, Lingling; Kong, Yunyi; Wang, Sheng; Li, Yong; Zhang, Sinong (Frontiers in Veterinary Science, 2023)
Crimean-Congo hemorrhagic fever (CCHF) is a zoonotic disease caused by Crimean-Congo hemorrhagic fever virus (CCHFV), which can cause severe clinical disease and even death in humans. In recent years, the disease has spread to a wider area, posing a major public health threat to China as well as the Middle East, Europe and Africa, and there is no safe and effective vaccine to prevent the disease. Recently, it has been shown that using the Zera fusion to target proteins can enhance immunogenicity and improve the potential for developing viral vaccines. Based on this finding, in this study, two vaccine candidates, Zera-Gn and Zera-Np, were prepared using an insect baculovirus system expressing CCHFV glycoprotein (Gn) and nucleocapsid protein (Np) fused with Zera tags, and evaluated for immunogenicity in BALB/c mice. The obtainedresults showed that both Zera-Gn and Zera-Np recombinant nanoparticles were successfully expressed, and Zera-Gn had good induction of humoral and cellular immunity in mice, and its immunogenicity was significantly higher than that of Zera-Np. The results indicated that Zera-Gn self-assembled nanoparticles prepared by fusing Zera tags with CCHFV spike-in protein Gn have the potential to be a candidate vaccine for CCHF, and this study provides a reference for the development of Zera self-assembled nanoparticle vaccine for CCHF.